Analisis kondisi vo2max pemain hockey indoor putri Gresik dalam menunjang keberhasilan meraih medali emas - Abdulloh, Ajeng Intan Mahardika; Widodo, Achmad; Wahyudi, Heri; Bawono, Mokhamad Nur; Susanto, Indra Himawan (Jurnal Porkes, 2023)
The VO₂Max condition of the Gresik women's indoor hockey players should be fulfilled. Since VO₂Max includes a baseline that represents general fitness which is good condition VO₂Max it can be assumed other physical endurance will follow. The purpose of this study was to find out the level of aerobic endurance (VO₂Max) possessed by Gresik women's indoor hockey players in supporting the success of winning a gold medal at Situbondo in 2022. Quantitative descriptive was used in this research method with 12 research subjects. The multi-stage fitness test (MFT) was used as an instrument in this study. The results of the analysis of aerobic endurance (VO₂Max) data from female indoor hockey players in the category "very poor" 0.00% (0 players), "less" 0.00% (0 players), "enough" 0.00% (0 players), “good” 50.00% (6 players), “very good” 41.70% (5 players) and “excellent” 8.30% (1 player). The average of this data analysis was 39.34. Based on these results, the level of aerobic endurance (VO₂Max) of Gresik women's indoor hockey players was in the “very good” category. It can be concluded that to meet good VO₂Max conditions, the results of this study can be used as a benchmark for other hockey teams when preparing for matches.